Detection of rickettsiae in fleas and ticks from areas of Costa Rica with history of spotted fever group rickettsioses - Troyo Rodríguez, Adriana (2016)
Outbreaks of spotted fevers have been reported in Costa Rica since the 1950s, although vectors responsible for transmission to humans have not been directly identified. In this study, species of Rickettsia were detected in ectoparasites from Costa Rica, mostly from five study sites where cases of spotted fevers have been reported. Ticks and fleas were collected using drag cloths or directly from domestic and wild animals and pooled according to species, host, and location. Pools were analyzed initially by PCR to detect a fragment of Rickettsia spp. specific gltA gene, and those positive were confirmed by detection of htrA and/or ompA gene fragments. Partial sequences of the gltA gene were obtained, as well as at least one ompA and/or ompB partial sequence of each species. Rickettsia spp. were confirmed in 119 of 497 (23.9%) pools of ticks and fleas analyzed. Rickettsia rickettsii was identified in one nymph of Amblyomma mixtum and one nymph of Amblyomma varium. Other rickettsiae present were ‘Candidatus Rickettsia amblyommii’ in A. mixtum, Amblyomma ovale, Dermacentor nitens, and Rhipicephalus sanguineus s. l.; Rickettsia bellii in Amblyomma sabanerae; Rickettsia felis in Ctenocephalides felis; and Rickettsia sp. similar to ‘Candidatus R. asemboensis’ in C. felis, Pulex simulans, A. ovale, and Rhipicephalus microplus. Results show the presence of rickettsiae in vectors that may be responsible for transmission to humans in Costa Rica, and evidence suggests exposure to rickettsial organisms in the human environment may be common. This is the first study to report R. rickettsii in A. varium and in A. mixtum in Costa Rica.